Corporate insolvency and liquidation - Chen, Wing Keong (2014)
In this competitive and forever changing business environment, business failures are inevitable. Thus, knowledge of Corporate Insolvency and Liquidation Laws will better inform affected parties about their positions, rights and enforcement of these rights in liquidation proceedings.